2003
DOI: 10.1021/bc034166b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Azacrown-Functionalized 2‘-O-Methyl Oligoribonucleotides, Potential Artificial RNases

Abstract: An improved synthesis for 3-(3-aminopropyl)- and 3-(3-mercaptopropyl)-1,5,9-triazacyclododecane has been developed and alternative methods for their conjugation to oligonucleotides have been described. Accordingly, the 3-aminopropyl azacrown and its N-(3-aminopropanoyl)-3-aminopropyl analogue have been tethered to the 3'-terminus of a 2'-O-methyloligoribonucleotide by aminolytic cleavage of the thioester linker utilized for the chain assembly. Studies on a monomeric model compound verify that the reaction proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…1 (33). Compound 32 was synthesized as described earlier (36,37). tert-Butyldimethylsilyl chloride (1.43 g, 9.5 mmol) was added to a mixture of 32 (2.4 g, 4.7 mmol) and a catalytic amount of imidazole in pyridine (20 mL).…”
Section: Methodsmentioning
confidence: 99%
“…1 (33). Compound 32 was synthesized as described earlier (36,37). tert-Butyldimethylsilyl chloride (1.43 g, 9.5 mmol) was added to a mixture of 32 (2.4 g, 4.7 mmol) and a catalytic amount of imidazole in pyridine (20 mL).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, it was shown that cleavage of RNA by lanthanide (La 3+ and Eu 3+ ) complex conjugated to antisense oligonucleotide (17) or by transition metal complexes conjugated to 2′- O -methyl oligoribonucleotides (18) occurs more efficiently when the target sequence is located within a bulge loop. Thus, oligonucleotide binding, yielding highly reactive bulge loops, can thus be considered as an approach to induction of unique reactive sites in RNA, which can be selectively cleaved by small catalytic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of other agents is selectively targeted against various stages of viral infection development and the life cycle of the virus, i.e., adsorption, penetra tion, synthesis of virus components, and the exit of daughter virions form cell. Agents that act upon virus genome are of particular interest; they include anti sense oligonucleotides [56], ribozymes [57], and RNases discussed here. These agents suppress virus production, but they are probably able to destroy latent virus infection.…”
Section: Mechanisms Of the Actionmentioning
confidence: 99%